2020
DOI: 10.1097/won.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

FOOTFIT Physical Activity mHealth Intervention for Minimally Ambulatory Individuals With Venous Leg Ulcers

Abstract: PURPOSE: The purpose of this study was to investigate the use of an mHealth application (app), self-management physical activity intervention FOOTFIT with an added patient-provider connectivity feature (FOOTFIT+), that was designed to strengthen the lower extremities of minimally ambulatory individuals with venous leg ulcers (VLUs). DESIGN: Randomized controlled trial. SUBJECTS AND SETTING: Twenty-four adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(45 citation statements)
references
References 28 publications
0
41
0
4
Order By: Relevance
“…However, another study had the opposite opinion 59 and reported that the ability of diseases‐specific tools to identify whether the changes in health‐related QoL caused by open ulcers and/or underlying causes were unclear. We did not identify any obvious differences between studies adopting generic instruments and diseases‐specific QoL instruments, and the QoL scores in intervention groups increased moderately after receiving PA/exercise interventions 44,46,49,51 . Overall, there was little variability in the instruments and metrics used to evaluate key outcomes of interest.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…However, another study had the opposite opinion 59 and reported that the ability of diseases‐specific tools to identify whether the changes in health‐related QoL caused by open ulcers and/or underlying causes were unclear. We did not identify any obvious differences between studies adopting generic instruments and diseases‐specific QoL instruments, and the QoL scores in intervention groups increased moderately after receiving PA/exercise interventions 44,46,49,51 . Overall, there was little variability in the instruments and metrics used to evaluate key outcomes of interest.…”
Section: Discussionmentioning
confidence: 74%
“…One study found a ‘significant difference’ in QoL scores between the intervention group and the control group on day 90 ( p = 0.03); however, supportive data were not provided 49 . One other study reported increased QoL scores in intervention group after receiving foot/ankle range of motion exercises 46 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations